2019
DOI: 10.1177/1179546819856855
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Interventions That Reduce Hospital Readmissions in Patients With Heart Failure; Towards the Identification of Change Agents

Abstract: Unplanned hospital readmissions are the most important, preventable cost in heart failure (HF) health economics. Current professional guidelines recommend that patient self-care is an important means by which to reduce this burden. Patients with HF should be engaged in their care such as by detecting, monitoring, and managing their symptoms. A variety of educational and behavioural interventions have been designed and implemented by health care providers to encourage and support patient self-care. Meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 73 publications
0
48
0
3
Order By: Relevance
“…In Korea, the prevalence of HF is expected to increase twofold, from 1.60% in 2015 to 3.35% in 2040 (Kim et al., 2017). Despite effective medical interventions, mortality and morbidity remain high, particularly among those aged 65 years and older (Toukhsati, Jaarsma, Babu, Driscoll, & Hare, 2019). HF constitutes an enormous economic burden for healthcare systems globally (Kessing et al, 2017; Toukhsati et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Korea, the prevalence of HF is expected to increase twofold, from 1.60% in 2015 to 3.35% in 2040 (Kim et al., 2017). Despite effective medical interventions, mortality and morbidity remain high, particularly among those aged 65 years and older (Toukhsati, Jaarsma, Babu, Driscoll, & Hare, 2019). HF constitutes an enormous economic burden for healthcare systems globally (Kessing et al, 2017; Toukhsati et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite effective medical interventions, mortality and morbidity remain high, particularly among those aged 65 years and older (Toukhsati, Jaarsma, Babu, Driscoll, & Hare, 2019). HF constitutes an enormous economic burden for healthcare systems globally (Kessing et al, 2017; Toukhsati et al., 2019). Optimal self‐care behaviours are vital to reduce adverse health outcomes among older patients with HF (Herber, Atkn, Stork, & Wilm, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have reported low adherence rates in self-care behaviors, due to the complexity of self-care and lifelong requirement of medical treatment [9,10]. Thus, many studies have evaluated various types of interventions to improve HF self-care behaviors and associated outcomes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados del estudio son comparables con los hallazgos de ECA que han examinado las intervenciones para mejorar el autocuidado en los adultos con FC (27)(28)(29)(30)(31)(32)(33)(34)(35). No fue posible analizar los resultados teniendo en cuenta la dosis y el contenido educativo por falta de datos.…”
Section: Discussionunclassified